Poor anticoagulation control in patients taking warfarin at a tertiary and district-level prothrombin clinic in Cape Town, South Africa - Ebrahim, Ismaeel (Division of Clinical Pharmacology, 2019)
Background. Warfarin is the most commonly used anticoagulant for both primary and secondary prevention of thromboembolism. For anticoagulation efficacy, the international normalised ratio (INR) needs to be within the therapeutic range for at least 65% of time on warfarin. Objectives. To describe INR control in patients on long-term warfarin and identified predictors of good INR control at two dedicated warfarin follow-up clinics in Cape Town, South Africa (SA). Methods. We reviewed clinical records of patients in care at the INR clinics at Mitchell’s Plain Community Health Centre and Groote Schuur Hospital. We included patients who had been on warfarin therapy for at least 27 months and excluded patients with <6 months of INR monitoring data or a >70-day gap between INR tests in the calculation period, and if >25% of follow-up time was at an alternative site. The time in therapeutic range (TTR) over 180 days using the Rosendaal method was calculated, and we categorised INR control as good if the TTR was ≥65%. We constructed a multivariate logistic regression model to identify associations with good INR control. Results. We included 363 patients, with a median age of 55 years (interquartile range (IQR) 44 - 64), of whom 65.6% were women. The most common indications for warfarin were valvular heart disease (45.7%) and atrial fibrillation (25.1%). The mean TTR was 47%, with only 91/363 patients having good INR control. In a multivariate model adjusted for age, sex, clinic and target INR, patients aged ≥55 years were more likely to have good INR control than younger patients (adjusted odds ratio 1.69, 95% confidence interval 1.03 - 2.79). Poorly controlled patients had more frequent INR monitoring than those with good INR control, with a median of 8 INRs (IQR 6 - 10) v. 6 INRs (IQR 5 - 8) in the 180-day period (p<0.0001). Conclusion. Only 25.1% of patients in our study achieved good INR control, despite regular INR monitoring. There is an urgent need to improve anticoagulation control of patients receiving warfarin in SA. Validated dosing algorithms are required, and access to lower warfarin dosage formulations may optimise individual dose titration. Advocacy for these formulations is advised.